Children's perspectives on health-promoting living environments: The significance of social capital. (August 2020) - Eriksson, Malin; Dahlblom, Kjerstin
Abstract: This article discusses the usefulness of social capital as a conceptual tool to design neighbourhoods promoting children's health. The aim was to explore children's perspectives of health promoting environments, and we used a combination of photovoice and grounded theory. Children from two neighbourhoods in a Swedish municipality were invited to photograph and discuss places of importance for their well-being. They presented places facilitating togetherness, enjoyable activities and positive emotions, mostly found in their immediate environments: at home, at school and in their neighbourhoods, but the access to these places was unequally distributed between the areas. The results highlight a need for ensuring all children's access to health promoting places and to include children's views in policy and planning. Investments in the physical environment need to be combined with efforts to influence norms and collective efficacy to secure local ownership and use of these investments. We found that the concept of social capital is a relevant conceptual tool for understanding what constitutes health-promoting places from children's perspectives and contributes to a deeper understanding on how physical and social environments are interlinked. Highlights: Local environments matters for children's self-perceived health and well-being. Places for togetherness, activities and positive emotions perceived as health promoting. Access to health promoting places is unequally distributed between neighbourhoods. Social capital relates to children's perspectives on health promoting places. Using social capital as a conceptual tool in policy requires including children's views.